Percutaneous ballon compression, a better choice for primary trigeminal neuralgia compared to microvascular decompression? - Shi, Yuwei; Liu, Wenhu; Peng, Shaopeng; Liu, Jianxiong (Frontiers in Surgery, 2025)
ObjectiveDemonstrate the superiority of percutaneous balloon compression (PBC) in the treatment of primary trigeminal neuralgia (PTN) compared to trigeminal microvascular decompression (MVD).MethodsClinical data, including immediate, short-term, and long-term pain relief, complications, duration of the operation, and postoperative hospital stay, were retrospectively analyzed for 114 patients diagnosed with PTN who were treated with either PBC or MVD between January 2018 and December 2021.ResultsThere were no statistically significant differences observed in the pain relief rates between the two surgical methods at 24 h postoperatively (MVD: 91.07%, PBC: 96.55%), at 6 months postoperatively (MVD: 87.5%, PBC: 94.8%), at 1 year postoperatively (MVD: 83.90%, PBC: 94.80%), and at 2 years postoperatively (MVD: 78.60%, PBC: 72.40%). However, the incidence of meningitis following MVD was significantly higher than that following PBC (P < 0.005). Additionally, both the duration of the operation and the length of the postoperative hospital stay in the MVD group were longer than those in the PBC group (P < 0.005).ConclusionPBC demonstrates efficacy comparable to MVD while offering a simpler procedure, improved safety, and a shorter postoperative hospital stay. Therefore, it may serve as a viable alternative to MVD and could become the preferred surgical approach for treating PTN in the future.